REVIEW OF LEGAL PROFESSIONAL ETHICS TOWARDS INVESTIGATORS IN THE CRIMINAL CASE OF FOUR STUDENTS REFUSING OMNIBUS LAW - Dea Iswandi; Fadillah Rizky Nur Ikhlas; Ilham Khoirudin Sanjaya; M. Hanif Muflih (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2021)
The way investigators handled students who were involved in thedemonstration to ratify the Job Creation Act did not reflect the slogan of